2009
DOI: 10.1080/00049530802579481
|View full text |Cite
|
Sign up to set email alerts
|

Measuring organisational climate and employee engagement: Evidence for a 7 Ps model of work practices and outcomes

Abstract: This study presents evidence supporting the psychometric properties of the Voice Climate Survey: an employee opinion survey that measures work practices and outcomes. The tool is tested across 13,729 employees from 1,279 business units representing approximately 1,000 organisations. Exploratory factor analyses, confirmatory factor analyses and internal reliability analyses support 31 lower-order work practices and outcomes that aggregate into seven higherorder work systems broadly covering practices and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 40 publications
4
75
0
3
Order By: Relevance
“…Because previous studies (Langford 2009;Havenga et al 2011) confirmed a four-factor solution for the GWA, and a one-factor solution did not make sense, it was decided to specify the four factors. A principal component analysis with a varimax rotation with Kaizer normalisation was used to analyse the factor structure of the GWA.…”
Section: According Tomentioning
confidence: 99%
“…Because previous studies (Langford 2009;Havenga et al 2011) confirmed a four-factor solution for the GWA, and a one-factor solution did not make sense, it was decided to specify the four factors. A principal component analysis with a varimax rotation with Kaizer normalisation was used to analyse the factor structure of the GWA.…”
Section: According Tomentioning
confidence: 99%
“…Prior research has shown that the individuals who are high on power distance accept hierarchy and embrace the leader's influence more fully than their low-PD counterparts (Den Hartog et al, 1999;Hofstede, 1980;Schaubroeck et al, 2007). Thus, teams composed of high-PD members provide a favorable climate for transformational leaders to exercise their inspiring influences and foster team members' dedication and engagement (Ehrhart & Klein, 2001;Langford, 2009). …”
Section: Hypothesis Testsmentioning
confidence: 99%
“…Organizational members working together on a regular basis come to develop shared values, forming a distinctive "team culture" (Levine & Moreland, 1991;O'Reilly, Chatman, & Caldwell, 1991). This value orientation shapes unique workplace climate, a platform upon which leadership is both exercised and processed (Langford, 2009). Research indicates that the impact of leadership varies appreciably by those workplace norms and values (Den Hartog et al, 1999;Ehrhart & Klein, 2001;Scandura & Dorfman, 2004;Schaubroeck et al, 2007).…”
Section: Hypothesis 1b: Transactional Leadership Is Negatively Associmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual may have a relatively stable 'average' level of engagement, yet will likely fluctuate significantly around this level across brief periods of time. Support for this proposition is drawn from a number of diary studies based on job demands-resources (JD-R) theory (Sonnentag et al, 2010) that have established an association between a range of factors including social support (Xanthpoulou, Bakker, Heuven, Demerouti, & Schaufeli, 2008), leadership style (Tims, Bakker, & Xanthopoulou, 2011;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2009), job resources (Breevaart, Bakker, & Demerouti, 2014) and personal resources such as self-efficacy and optimism (Xanthopoulou et al, 2008;2009), and engagement at the between-person level.…”
Section: Engagement Within the Working Daymentioning
confidence: 99%